2021
DOI: 10.3389/fpls.2021.767140
|View full text |Cite
|
Sign up to set email alerts
|

L-Cysteine Increases the Transformation Efficiency of Chinese Cabbage (Brassica rapa ssp. pekinensis)

Abstract: Successful Agrobacterium-mediated transformations of Chinese cabbage have been limited owing to the plant’s recalcitrant nature, genomic background and explant necrosis upon infection, which hinders the transfer of T-DNA region into the Chinese cabbage. Consequently, in the current experiment, a stable Agrobacterium tumefaciens-mediated transformation method for Chinese cabbage cv. Kenshin established by employing important anti-oxidants in the co-cultivation and subsequent regeneration media. Four-day-old in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Comparing the substrata used for acclimatization of in vitro-derived kale microplantlets, the highest survival rate result from a mixture of soil and perlite (1:1). Successful acclimatization in a mixture containing perlite was also reported for cabbage (soil:perlite, 3:1) and Chinese cabbage (perlite alone) (Gerszberg et al 2015;Sivanandhan et al 2019). Perlite is well-known for soil aeration and water absorption (Ilahi and Ahmad 2017), thus mixture with perlite is the easiest way to provide optimal conditions for microplantlets.…”
Section: Resultsmentioning
confidence: 81%
“…Comparing the substrata used for acclimatization of in vitro-derived kale microplantlets, the highest survival rate result from a mixture of soil and perlite (1:1). Successful acclimatization in a mixture containing perlite was also reported for cabbage (soil:perlite, 3:1) and Chinese cabbage (perlite alone) (Gerszberg et al 2015;Sivanandhan et al 2019). Perlite is well-known for soil aeration and water absorption (Ilahi and Ahmad 2017), thus mixture with perlite is the easiest way to provide optimal conditions for microplantlets.…”
Section: Resultsmentioning
confidence: 81%
“…Moreover, the high transformation efficiencies for B. napus-RC plants is a substantial improvement compared to recent studies, which reported transformation efficiencies of 1.4-3% (Min et al 2007), 2.89-5% (Lee et al 2004), 1.2% (Konagaya et al 2013), 15% (Baskar et al 2016) from hypocotyl explants and 10.83% (Li et al 2021) and 14% (Sivanandhan et al 2021) from explants from cotyledons of Brassica rapa L. ssp. pekinensis.…”
Section: Rapid Cycling Plants: An Effective Trait Testing Platform Fo...mentioning
confidence: 70%
“…2016) from hypocotyl explants and 10.83% (Li et al . 2021) and 14% (Sivanandhan et al . 2021) from explants from cotyledons of Brassica rapa L. ssp .…”
Section: Discussionmentioning
confidence: 99%
“…Chinese cabbage (Brassica rapa L.) is one of the most important green leafy vegetables in the family Brassicaceae with increasing popularity in the world (Sivanandhan et al, 2021;Vanjildorj et al, 2009). Rapeseed (Brassica napus L.) is also one of the most widely grown crops of Brassicas in the world and is the second most important crop after cereal in the Czech Republic (Anonymous, 2018).…”
Section: Introductionmentioning
confidence: 99%